Male‐specific DNA markers provide genetic evidence of an XY chromosome system, a recombination arrest and allow the tracing of paternal lineages in date palm. Issue 2 (11th December 2012) - Cherif, Emira; Zehdi, Salwa; Castillo, Karina; Chabrillange, Nathalie; Abdoulkader, Sabira; Pintaud, Jean‐Christophe; Santoni, Sylvain; Salhi‐Hannachi, Amel; Glémin, Sylvain; Aberlenc‐Bertossi, Frédérique
Summary: Whether sex chromosomes are differentiated is an important aspect of our knowledge of dioecious plants, such as date palm ( Phoenix dactylifera ). In this crop plant, the female individuals produce dates, and are thus the more valuable sex. However, there is no way to identify the sex of date palm plants before reproductive age, and the sex‐determining mechanism is still unclear. To identify sex‐linked microsatellite markers, we surveyed a set of 52 male and 55 female genotypes representing the geographical diversity of the species. We found three genetically linked loci that are heterozygous only in males. Male‐specific alleles allowed us to identify the gender in 100% of individuals. These results confirm the existence of an XY chromosomal system with a nonrecombining XY‐like region in the date palm genome. The distribution of Y haplotypes in western and eastern haplogroups allowed us to trace two male ancestral paternal lineages that account for all known Y diversity in date palm. The very low diversity associated with Y haplotypes is consistent with clonal paternal transmission of a nonrecombining male‐determining region. Our results establish the date palm as a biological model with one of the most ancient sex chromosomes in flowering plants.